Epidemiological characteristics and antimicrobial resistance of extensively drug-resistant Acinetobacter baumannii in ICU wards - Jingchao Shi; Xiaoting Mao; Fengtian Sun; Jianghao Cheng; Lijia Shao; Xiaoyun Shan; Yijun Zhu (Microbiology Spectrum)
ABSTRACT Acinetobacter baumannii is a significant nosocomial pathogen, particularly problematic due to its extensive drug resistance. This study investigates 56 extensively drug-resistant A. baumannii (XDRAB) strains collected from various ICU wards at Jinhua Central Hospital, Zhejiang Province, China. Strains were isolated from diverse clinical samples, including sputum, blood, cerebrospinal fluid, and wound secretions. Identification was confirmed via matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS), and antibiotic susceptibility testing was conducted using the VITEK 2 Compact system, E-test, and Kirby-Bauer methods. All strains were susceptible to polymyxin, with four showing intermediate susceptibility to tigecycline, while resistance rates to other antibiotics were 100%. Molecular typing through pulsed-field gel electrophoresis (PFGE) classified the strains into 10 types, with the dominant type (G) primarily found in ICU3, indicating a potential clonal outbreak. Whole-genome sequencing (WGS) and multi-locus sequence typing (MLST) identified ST208 as the predominant sequence type. Resistance gene screening revealed the presence of blaOXA-23, blaTEM-1D, and aminoglycoside resistance genes in most strains. Phylogenetic analysis confirmed the clonal transmission of ST208 strains across the hospital, with a high degree of genomic similarity among the isolates. These findings highlight the importance of continuous monitoring and effective infection control measures to prevent the spread of XDRAB in healthcare settings.IMPORTANCEExtensively drug-resistant Acinetobacter baumannii is a critical public health threat, particularly in hospital environments where it causes a variety of infections. The global spread of extensively drug-resistant A. baumannii (XDRAB) and its resistance to most antibiotics make treatment options limited, increasing the risk of patient morbidity and mortality. This study provides important insights into the molecular epidemiology of XDRAB in a hospital setting, revealing the clonal transmission of the ST208 sequence type. By utilizing both pulsed-field gel electrophoresis (PFGE) and whole-genome sequencing (WGS), we identified genetic links between strains and the presence of key resistance genes. The findings underscore the urgent need for robust infection control protocols, routine surveillance, and judicious use of antibiotics to mitigate the spread of XDRAB and ensure better patient outcomes.